2012
DOI: 10.31357/jtfe.v2i2.594
|View full text |Cite
|
Sign up to set email alerts
|

Agarwood-type Resin from Gyrinops walla Gaertn: A New Discovery

Abstract: Agarwood is an expensive resinous product extracted from some members of Aquilaria and Gyrinops species of the family Thymalaeaceae. Agarwood essential oil is a highly valued perfumery product in modern cosmetics and traditional Attar. Agarwood extraction from the above species and product manufacturing are done in India and Southeast Asian countries. However, overharvesting, low natural regeneration, and legal restrictions at present, have limited the supply of this product.Gyrinops walla is recorded in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…The ability of G. walla in producing agarwood was explored for the first time http://dx.doi.org/10.1016/j.indcrop.2015.01.060 0926-6690/© 2015 Elsevier B.V. All rights reserved. through our previous research (Subasinghe et al, 2012;Subasinghe and Hettiarachchi, 2013). These findings confirmed that G. walla is producing agarwood type resins which are chemically similar to that of Aquilaria species.…”
Section: Introductionmentioning
confidence: 96%
“…The ability of G. walla in producing agarwood was explored for the first time http://dx.doi.org/10.1016/j.indcrop.2015.01.060 0926-6690/© 2015 Elsevier B.V. All rights reserved. through our previous research (Subasinghe et al, 2012;Subasinghe and Hettiarachchi, 2013). These findings confirmed that G. walla is producing agarwood type resins which are chemically similar to that of Aquilaria species.…”
Section: Introductionmentioning
confidence: 96%
“…Even if this species has been recorded in some areas of South India, at present Gyrinops walla can only be seen in Sri Lanka (Subasinghe, Hettiarachchi & Rathnamalala, 2012). As there are many freely growing Gyrinops walla trees in the Kudawa-Sinharaja site, paid local people enter the site looking for these trees to extract its resin.…”
Section: Biopiracy Challenges and Cbetmentioning
confidence: 99%
“…To date, only three species are known agarwood producers: G. ledermannii , G. versteegii , and G. walla (Hou 1960 ;Ng et al 1997 ;Compton and Zich 2002 ;Subasinghe et al 2012 ). The genus Gyrinops was listed under Appendix II of CITES in 2005 together with the genus Aquilaria as a conservation effort; however, it was not included in the IUCN Red List perhaps because the exploitation of its natural population was not as alarming as Aquilaria .…”
Section: Brief Notes On Gyrinops a Closely Related Genusmentioning
confidence: 99%
“…Gyrinops plantations were initiated as early as 1998 without prior information on its taxonomy. A thorough taxonomy study was then carried out in 2001 where the plantation species was identifi ed as G. ledermannii (Subasinghe et al 2012 ).…”
Section: Brief Notes On Gyrinops a Closely Related Genusmentioning
confidence: 99%